SANITARY STATE OF BEECH STANDS IN NATIONAL NATURAL PARK “ZACHAROVANYY KRAY” - Shyshkanynets, І. F. (Forestry and Forest Melioration, 2018)
Introduction The research conducted using ICP-Forest method showed that from 1991 to 2009 common beech stands in the Ukrainian Carpathians had a strong tendency towards deterioration. However, one can observe a slight improvement in the situation with common beech in the Ukrainian Carpathians over the past 5 years. In view of the fact that on the territory of NNP “Zacharovanyy Kray” the forests containing beech is the predominant plant system (92% of the area covered with forest vegetation), the assessment of their condition is important. It is needed for predicting the process of their weakening, as well as for the development of forest management (except for the preserved area of 1332.1 hectares) in order to improve the stability and productivity of forest stands. Materials and methods The objects of research were common beech forest stands of different age categories in the moist fertile forest site which is the most common site type (87.3 %). Assessment of the health condition of the beech stands was carried out in the summer months (July-August) 2015 in 14 sample plots through their detailed examination. While examining the forest stands, the category of the sanitary state of all trees in the sample plots, loss of assimilation system and disease manifestation were assessed. To assess defoliation the Atlas of forest trees assimilation apparatus loss was used. Based on defoliation of the trees the average value was determined for the woody species and the forest stands, and the forest stand was attributed to one of the five levels of damage: 0 – no damages (defoliation is ? 10 %); 1 – slightly damaged (11–25 %); 2 – medium damaged (26–60 %); 3 – extremely damaged (61–90 %); 4 – dead (91–100 %). The index of the forest sanitary state was calculated as the weighted average by condition categories using the corresponding formula. Results Index of sanitary state of the beech stands varies between 1.37 and 3.30. The middle-aged beech stands are characterized by the best condition, their index varies between 1.37 and 1.96. The index of forest condition of mature compound beech stands is a little higher and ranges from 1.66 to 2.20. Sanitary condition of single-storeyed beech stands of approaching maturity and virgin forests is poorer and ranges from 2.18 to 2.33 and from 2.59 to 3.30, respectively. As for the degree of dominance, the beech trees in the sample plots are characterized by an average 2.5 Kraft class. It has been found out that there is a close correlation between Kraft class and defoliation index (r = 0.90) and between Kraft class and sanitary state, (r = 0.88). The number of damaged trees in the sample plots varies from 2 (in the second sample plot) to 32 (in the fifth sample plot). As for intensity, only the first and fifth plots have damages exceeding 25 %. By type of damage, the side-dry trees quantitatively prevail in the sample plots (0–15 %). The share of trees with water shoots is more significant and varies between 12 and 63 %. The calculated multiple correlation coefficients for defoliation and sanitary condition index showed that there is very strong relationship between the stand density and Kraft class (r = 0.91; 0.93, respectively); the correlation ratio between the stand density and the age of the stands is fairly high (r = 0.68) and high (r = 0.79). Conclusions By the health condition, the beech stands of National Natural Park “Zacharovanyy Kray” are weakened and slightly damaged as for the degree of degradation of their photosynthetic apparatus. Virgin forests are much weakened and moderately damaged, respectively. This state of virgin forests, according to the author, corresponds to one of the phases of their development, namely aging. The share of damaged trees in the sample plots ranges from 2 to 32 %. By type of damage, side-dry trees quantitatively prevail in the sample plots (0–15 %). The share of trees with water shoots ranges between 12 and 63 %.